Marketing before patenting: implications for price controls in Canada - Lexchin, Joel (Open Medicine Publications, Inc., 2010)
The Patented Medicine Prices Review Board (PMPRB) regulates the introductory price of new patented medications in Canada. Some drugs are marketed before they are patented and are therefore outside the authority of the PMPRB. This study was undertaken to determine how many drugs fall into this category, the time period between marketing and patenting, and the excess revenue, if any, earned before prices are subject to regulation. Between 2000 and 2008 a total of 42 drugs were marketed before being patented. Complete data were not available for 9 of these, leaving 33 of the 42 for analysis. Drugs were potentially being marketed between 54 and 2707 days before they came under PMPRB jurisdiction. Three products were eventually deemed to have exceeded the maximum introductory price, and the total excess revenue for these 3 was $9,289,688. Although only 3 of 33 drugs were found to be overpriced, the fact that prices can go unregulated for up to 7.4 years is troublesome. If companies are charging excessive prices, then the additional payments they receive may limit the ability of provincial formularies to list additional drugs. Controlling prices on the basis of patent status has significant limitations, and a new system that deals with prices of all medications should be developed.